PENGARUH TINGKAT LMX (Leader-Member Exchange) DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN RUMAH SAKIT UMUM DAERAH (RSUD) dr. ZAINOEL ABIDIN BANDA ACEH - Nurul Dhatul Maula (SI-MEN, 2014)
The aim of this research was to examine the influence of LMX (Leader-Member Exchange) and Work Environment on Staff’s Job Satisfaction. This research took place at Zainoel Abidin State Hospital, Banda Aceh and involved 170 respondents as the sample. Primary data was collected by spreading questionnaire sheets and was analyzed by multiple regression linear. The object of this study was LMX (Leader-Member Exchange) and Work Environment towards Zainoel Abidin State Hospital Staff’s Job Satisfaction. Sample was drawn using cluster random sampling where population was divided into clusters and sample was selected from the smallest unit; thus population of the cluster is subpopulation of the total population. The results showed that F count > F table and therefore, the alternative hypothesis (Ha) was accepted while the null hypothesis (H0) was rejected. Therefore, it was concluded that LMX (X1) and Work Environment (X2) had a significant influence on dr. Zainoel Abidin State Hospital Staff’s Job Satisfaction. F-calculated value of 66.666. The coefficient of determination (R2) of 0.444 obtained by means variable LMX (Leader-Member Exchange) and work environment are able to explain 44,4% of the variable Job Satisfaction and the remaining 55,6% is explained by other variables.